Art and Material Culture as Instruments of Gendered Self-Fashioning in the Life of Isabel Farnesio (1692-1766) - Cosgrove, Aoife Jane (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2024)
This thesis takes as its central focus Isabel Farnesio, exploring the ways in which her engagement with art reflected and buttressed her construction of identity. Born Elisabetta Farnese, the Princess of Parma in 1692, and elevated to the status of Queen of Spain upon her marriage to King Felipe V in 1714, Isabel ruled for more than thirty years as queen and lived some twenty years more as a widow, passing away in the year 1766. This thesis reveals the roles that gender and self-fashioning played in Isabel's extensive collecting of art and material culture. During the entirety of her life Isabel demonstrated a strong interest in art, and regularly commissioned, collected, and created works of art with which she decorated her residences. By studying extant works of art, archival material, and inventories, as well as eighteenth-century texts and modern scholarship, new perspectives can be proposed regarding the ways in which Isabel interacted with works of art in a variety of media. Comprised of four chapters which study Isabel's portraiture, amateur artistic production, collecting of fine art, and collecting of luxury objects respectively, this thesis examines the evidence of self-fashioning which can be discerned within these areas and proposes that Isabel's nationality, rank, and gender all played a role in the development of her tastes and the construction of her identity.
APPROVED
Keywords: self-fashioning; Isabel Farnesio; Elisabetta Farnese; gender; queenship; collecting; Spain; widowhood; eighteenth century; Bourbons